Associations between interpersonal violence and cigarette smoking, e-cigarette use, and dual use among Mexican adolescent students - Rodríguez-Bolaños, Rosibel; Díaz-Andrade, Evangelina; Ramírez-Palacios, Paula; Rojas-Carmona, Anabel; Gallegos-Carrillo, Katia; Barrientos-Gutiérrez, Inti; Cruz-Jiménez, Lizeth; Vidaña-Pérez, Dèsirée; Arillo-Santillán, Edna; Thrasher, James F. (Frontiers in Public Health, 2025)
ObjectiveTo assess associations between experienced violence and the use of combustible cigarettes, e-cigarettes, and of both products (“dual use”) among adolescent students from Mexico.MethodsData comes from an online survey among 3,046 adolescents (12–19 years) conducted between September and December 2021. Students reported experiences of neglect, physical, psychological, and sexual violence perpetrated by household members, and digital violence (by anyone) in the previous 12 months, as well as current (last 30 day) use of cigarettes and e-cigarette. In multinomial logistic models, exclusive cigarette use, exclusive e-cigarette use, and dual use (reference = no use) were regressed on experienced violence and covariates.ResultsThe prevalence of exclusive use of cigarettes was 1.4%, exclusive e-cigarette use was 6.1, and 2.4% for dual use. Almost half (46.9%) of adolescents reported having been the target of physical violence, followed by psychological violence (42.6%), neglect (34.9%), digital violence (12.3%), and sexual violence (5.2%). In adjusted multinomial models, adolescents who experienced physical violence (Adjusted Relative Risk Ratios: ARRR = 2.28, 95% CI [1.05–4.96]) were more likely to exclusively smoke cigarettes. Adolescents were also more likely to exclusively use e-cigarettes if they had been targeted by psychological or digital violence (ARRR = 1.55, 95% CI [1.05–2.29] and ARRR = 1.69, 95% CI [1.12–2.54], respectively). Experience of physical, digital, neglect, and sexual violence were positively associated with dual use.ConclusionExperiences of violence may increase the likelihood of tobacco use, particularly dual use. Prevention programs may need to include the family environment to reduce violence.